The Effect of a Polysaccharide-Based Multinutrient Dietary Supplementation Regimen on Infections and Immune Functioning in Multiple Sclerosis. (3rd March 2020) - Reginald McDaniel, H.; LaGanke, Christopher; Bloom, Laura; Goldberg, Sharon; Lages, Lucas C.; Lantigua, Laura A.; Atlas, Steven E.; Woolger, Judi M.; Lewis, John E.
Abstract: Multiple sclerosis (MS) is a progressive neurodegenerative disease associated with increased infection rates, chronic inflammation, and premature death. Optimization of nutritional status via dietary supplementation may improve immune function in people suffering from MS and lead to decreased rates of infection. Fifteen individuals with a diagnosis of relapsing-remitting MS for an average of 12.4 years (SD =7.4; R = 2, 25) were enrolled in a one-year open-label clinical trial. Participants consumed a broad-spectrum dietary supplement regimen containing polysaccharides, phytochemicals, antioxidants, vitamins, and minerals three times per day. The occurrence of infections and a panel of cytokines, growth factors, and T- and B-cell subsets were assessed at baseline and 12 months. Seven female and 8 male participants with an average age of 51.3 years (SD =7.2; R = 38, 65) completed the study. At the end of the intervention, participants had fewer total infections (M = 7.9, SD =8.1 at baseline and M = 2.5, SD =4.3 at 12-month follow-up). At 12 months, IL-2, TNF-α, EGF, and CD95 + CD34+ significantly increased, while IL-1β significantly decreased. No major adverse effects were reported; only mild gastrointestinal intolerance was reported in four cases. A decreased occurrence of infection was observed in MS patients treated with 12 months of a polysaccharide-based multinutrient dietary supplement. Significant changes were also noted in several key biomarkers that would be physiologically favorable to the MS population. Thus, the results of this study suggest an immunomodulatory effect of the dietary supplement regimen studied.